The Use of Pulse Frequency Modulation Technique for Optical Video Communication System - Al-Naimee, K. A.; Taleb, A. M.; Gubashi, H. J. (Iraqi Journal of Laser, 2003)
An optical video communication system is designed and constructed using pulse frequency modulation (PFM) technique. In this work PFM pulses are generated at the transmitter using voltage control oscillator (VCO) of width 50 ns for each pulse. Double frequency, equal width and narrow pulses are produced in the receiver be for demodulation. The use of the frequency doubling technique in such a system results in a narrow transmission bandwidth (25 ns) and high receiver sensitivity.